2015
DOI: 10.1097/mib.0000000000000405
|View full text |Cite
|
Sign up to set email alerts
|

Donor Recruitment for Fecal Microbiota Transplantation

Abstract: Recruitment of fecal donors for FMT is challenging with only a small percentage ultimately serving as donors. Many were unable or unwilling to meet the donor commitment requirements. A surprisingly large proportion of healthy asymptomatic donors failed stool testing, primarily due to gastrointestinal parasites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
121
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(135 citation statements)
references
References 34 publications
8
121
1
5
Order By: Relevance
“…Although blood donors represent a healthy subset of the general population, more than half of all included blood donors failed the initial pre-screening. The high exclusion rate in our study is similar to that reported by others, 14 , 15 but unlike the previous studies, we excluded donors that presented any forms of allergy and lowered the upper BMI limit to 28 kg/m 2 to further reduce the risk of potential risk factors. 19 Correspondingly, including these parameters markedly increased our pre-screening exclusion rate.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Although blood donors represent a healthy subset of the general population, more than half of all included blood donors failed the initial pre-screening. The high exclusion rate in our study is similar to that reported by others, 14 , 15 but unlike the previous studies, we excluded donors that presented any forms of allergy and lowered the upper BMI limit to 28 kg/m 2 to further reduce the risk of potential risk factors. 19 Correspondingly, including these parameters markedly increased our pre-screening exclusion rate.…”
Section: Discussionsupporting
confidence: 73%
“…7 , 14 , 15 , 18 Still, the recruitment of eligible feces donors remains challenging. Although blood donors represent a healthy subset of the general population, more than half of all included blood donors failed the initial pre-screening.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations